I have been working on the solution to the following differential equation:

$$y' + y = \frac{2x}{e^x(1+ye^x)}$$

I am not sure how to solve this type of problem because of the y on the right side... I tried to multiply both sides by the bottom. From there I tried to find the solution as though it were:

$$(1+ye^x)y' + y(1+ye^x) = 0$$

However, I thought that this method of solution required the $y'$ to be isolated. If that is not the case, then I am solving it fine. If that is the case, then what am I meant to be doing?

  • $\begingroup$ The solution is of the form $y = -e^{-x} - \sqrt{x^2 + C}$. Plug and verify. $\endgroup$ – Ahmad Bazzi Aug 25 at 22:00
  • $\begingroup$ Can you explain how you got that? $\endgroup$ – dminzi Aug 25 at 22:06
  • 1
    $\begingroup$ Your homogeneous equation can be factored and as such can be easily solved. $\endgroup$ – Allawonder Aug 25 at 22:10
  • $\begingroup$ @AhmadBazzi You're sure that's the general solution? No other functions satisfy the equation? $\endgroup$ – Allawonder Aug 25 at 22:12
  • 1
    $\begingroup$ @dminzi I mean that the second equation in OP is trivial since it implies $y'=-y$ or $y=-e^{-x}.$ So well, you'd be right to cancel since the latter doesn't satisfy the original equation in any case. $\endgroup$ – Allawonder Aug 25 at 23:08

Let $$y=ue^{-x}$$


Your differential equation transforms into

$$u'=\frac {2x}{1+u}$$ Which is separable.

$$\int (1+u)du = \int 2x dx$$

Solve for $u$ and substitute in $y=ue^{-x}$ to find $y$


$$y' + y = \frac{2x}{e^x(1+ye^x)}$$ $$\implies \{ye^x(1+ye^x)-2x\}dx+e^x(1+ye^x)dy=0$$ which is of the form $$M(x,y)dx+N(x,y)dy=0$$ where $$M(x,y)=ye^x(1+ye^x)-2x\qquad \text{and}\qquad N(x,y)=e^x(1+ye^x)$$ Now $$\frac{\partial M}{\partial y}=e^x+2ye^{2x}\qquad \text{and}\qquad \frac{\partial N}{\partial x}=e^x+2ye^{2x}$$ Clearly, $$\frac{\partial M}{\partial y}=\frac{\partial N}{\partial x}$$ So the given differential equation is exact differential equation and its solution is $$\int_{\text{treating $~y~$} as constant}M~dx~+~\int(\text{terms in $~N~$not containing $~x~$})~dy~=~c$$ $$\implies \int_{\text{treating $~y~$} as constant}\{ye^x(1+ye^x)-2x\}~dx~+~\int0~dy~=~c$$ $$\implies ye^x~+~\frac{1}{2}y^2~e^{2x}-x^2~=~c$$ $$\implies y=\frac{-e^x\pm\sqrt{e^{2x}- 2~e^{2x}\cdot (-x^2-c)}}{e^{2x}}$$ $$\implies y=\frac{-1\pm\sqrt{1- 2(-x^2-c)}}{e^{x}}$$ where $~c~$is constant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.